Temporal Trends of High‐Intensity Statin Therapy Among Veterans Treated With Percutaneous Coronary Intervention. Issue 5 (4th March 2018) - Bin Abdulhak, Aref A.; Vaughan‐Sarrzin, Mary; Kaboli, Peter; Horwitz, Phillip A.; Mosher, Hilary; Sigurdsson, Gardar; Walker, Nicholas E.; Wallace, Robert; Robinson, Jennifer G.
Abstract : Background: The 2013 American College of Cardiology/American Heart Association blood cholesterol guideline recommends high‐intensity statin therapy among certain groups of patients, but full implementation of the guideline has not yet been satisfactory. We aimed to investigate the temporal trends and predictors of high‐intensity statin therapy among veterans who had been treated with percutaneous coronary intervention (PCI) and followed up by cardiologists within the Veterans Health Administrative system. Methods and Results: A retrospective cohort study was conducted at the Veterans Health Administrative system including all patients >18 years old who had their PCI procedure between October 2010 and September 2016. National Veterans Health Administrative databases were used to retrieve study participant's demographics, comorbid conditions, statin type and dose within 90 days before and after the PCI procedure. There were 48 862 patients who underwent a PCI procedure during the study period. High‐intensity statin use at 90 days post‐PCI rose from 23% in 2010 to 37% before release of the 2013 American College of Cardiology/American Heart Association cholesterol guideline, then rose sharply to 80% by 2016. The projected 10‐year risk of arteriosclerotic cardiovascular disease events among our study population was projected to be ≈1841 fewer if the cohort had received high‐intensity statin therapy versus moderate‐intensity statin. Conclusions: By 2016, the 2013 American College of Cardiology/American Heart Association blood cholesterol guideline was well implemented among veterans who had a PCI procedure in the Veterans Health Administrative system, suggesting systems of care can be improved to increase rates of high‐intensity statin initiation.